PENGARUH FAKTOR PRIBADI DAN PSIKOLOGI TERHADAP KEPUTUSAN MENABUNG DI BANK NAGARI CABANG PANGKLAN - Lasri Utami; Suarman '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research to investigate the influence of personal and psychological factors on the decision to save in Nagari Bank Branch Pangkalan. This research was conducted in Nagari Bank Branch Pangkalan which is located in Jorong Pasar Baru Kecamatan Pangkalan Baru Koto, Kabupaten 50 Kota, West Sumatra. With a sample of 97 customers using the formula slovin. The research instrument used was a questionnaire by using descriptive data analysis and regression. From the results of research using descriptive analysis known that personal factors most respondents are at very high category as many as 64 respondents or 65.97%. This means customers found personal factors influence a client's decision to save in Nagari Bank Branch Pangkalan. For psychological factors that most respondents are in the high category, only 40 respondents or 41.23%. The percentage impact that psychological factors are still under 50%. This means that the client believes that psychological factors do not affect the customer's decision to save in Nagari Bank Branch Pangkalam. Using statistical analysis known that personal and psychological factors influence simultan toward saving decision (Fhitung 27.484> Ftabel 3.09). While partially personal factors significantly influence decision-saving (thitung 5,249> t table 1.661) whereas psychological factors did not significantly influence the decision to save (thitung 0.444 <t table 1.661). From the calculation of the coefficient of determination of personal and psychological factors have an influence on the decision to save Bank Nagari Base Branch of 35.6% and the remaining 64.4% is influenced by other factors not examined. Thus the expected Bank Nagari improve personal and psychological factors that may influence the decision to save the customer.Keywords: Influenced, Personal Factors, Psychological Factors, The Decision To Save